2020
DOI: 10.21203/rs.3.rs-36659/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered Metabolism of Mothers of Young Children with Autism Spectrum Disorder: A Case Control Study

Abstract: Background: Previous research studies have demonstrated abnormalities in the metabolism of mothers of young children with autism.Method: Metabolic analysis was performed on blood samples from 30 mothers of young children with Autism Spectrum Disorder (ASD-M) and from 29 mothers of young typically-developing children (TD-M). Targeted metabolic analysis focusing on the folate one-carbon metabolism (FOCM) and the transsulfuration pathway (TS) as well as broad metabolic analysis were performed. Statistical analysi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Conversely, if both B12 and folate were low, the risk of ASD was also increased (OR = 2.4). Another study of maternal blood levels at 2-5 years after birth found that mothers of children with ASD had 25% lower levels of vitamin B12 compared to mothers of typical children, p = 0.003; so, investigation of their B12 levels during pregnancy is warranted [72].…”
Section: B12 (Cobalamin) Researchmentioning
confidence: 99%
“…Conversely, if both B12 and folate were low, the risk of ASD was also increased (OR = 2.4). Another study of maternal blood levels at 2-5 years after birth found that mothers of children with ASD had 25% lower levels of vitamin B12 compared to mothers of typical children, p = 0.003; so, investigation of their B12 levels during pregnancy is warranted [72].…”
Section: B12 (Cobalamin) Researchmentioning
confidence: 99%